Comparative analysis of uterine flora in pregnant women undergoing elective and non-elective caesarean section of central Uttar Pradesh, India - Swapnil Golus; Shyam Pyari Jaiswar; Seema Mehrotra; Deepak Anand (Journal of Family Medicine and Primary Care)
Context: The incidence rate of puerperal infection caused by uncommon pathogenic bacteria has risen. Thus, we sought to analyse uterine flora in patients of elective and non-elective caesarean section. Aims: (1) To compare uterine flora in elective and non-elective caesarean section. (2) To find the association of puerperal infection and neonatal sepsis with selected variables. Settings and Design: Prospective cohort study. Materials and Methods: A total of 150 elective and 150 non-elective caesarean cases were selected. Intraoperatively, soon after birth, a uterine swab and a placental tissue sample were collected and sent for bacterial culture testing. In addition to the uterine and placental findings, sociodemographic parameters were recorded and compared. Statistical Analysis Used: Data were entered in Microsoft Excel and analysed using the Statistical Package for Social Sciences (SPSS). Results: Positive uterine cultures were detected in 8.67% of elective and 21.33% of non-elective caesarean sections. Positive placental culture was found in 5.33% of elective and 12.00% of non-elective cases. Escherichia coli was the most commonly found bacteria in positive uterine swab and placental tissue cultures. In the non-elective group, women with positive cultures had substantially more puerperal infections and neonatal sepsis. Conclusions: Collecting routine intrauterine cultures during elective and non-elective caesarean sections will be effective for detecting the type of bacteria and treatment. It will be better to counsel the patient for opting elective caesarean section prior to the onset of labour.